Comparison of physiology and kinematics between a single-leg para-alpine skier and a two-legged skier - Ommen, J.; Turczyn, D.; Graham, D.; Seifert, J. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: The physiology and mechanics of single-leg skiers are not well understood; there is one previous study on this group of skiers. Single-leg skiers undergo greater knee extension and recruitment of biceps femoris for balance during alpine skiing, but trunk kinematics and muscle recruitment have not been extensively studied 1. The purpose of this study is to identify kinematic and muscular activation differences between single-leg skiers and non-disabled skiers.